2009
DOI: 10.1016/j.bpj.2008.12.3932
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Dynamics of Halorhodopsin Studied by Time-Resolved Diffusion

Abstract: Reaction dynamics of a chloride ion pump protein, halorhodopsin (HR), from Natronomonas pharaonis (N. pharaonis) (NpHR) was studied by the pulsed-laser-induced transient grating (TG) method. A detailed investigation of the TG signal revealed that there is a spectrally silent diffusion process besides the absorption-observable reaction dynamics. We interpreted these dynamics in terms of release, diffusion, and uptake of the Cl(-) ion. From a quantitative global analysis of the signals at various grating wavenum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…This conclusion is credible because of the following two facts: Only the O intermediate has a redshifted absorption spectrum and removal of Cl − from NpHR in the dark shows redshift due to disappearance of electrical interaction of Cl − and positively charged protonated Schiff base. The same conclusion was also reported using a transient grating experiment where the Cl − diffusion signal was detected synchronously with the appearance of O [16]. Furthermore, FTIR spectroscopy suggested structural similarity between the O intermediate and the anion-free unphotolyzed state [17].…”
Section: Introductionsupporting
confidence: 77%
“…This conclusion is credible because of the following two facts: Only the O intermediate has a redshifted absorption spectrum and removal of Cl − from NpHR in the dark shows redshift due to disappearance of electrical interaction of Cl − and positively charged protonated Schiff base. The same conclusion was also reported using a transient grating experiment where the Cl − diffusion signal was detected synchronously with the appearance of O [16]. Furthermore, FTIR spectroscopy suggested structural similarity between the O intermediate and the anion-free unphotolyzed state [17].…”
Section: Introductionsupporting
confidence: 77%
“…[1][2][3] To date, HR homologs from Halobacterium salinarum and Natronomonas pharaonis have been extensively investigated. [4][5][6][7][8][9][10][11][12][13][14] In H. salinarum, which possesses the light-driven proton pump bacteriorhodopsin (BR) as a principal component in the bioenergetic system, HR is believed to play a role in maintaining osmotic balance during cell growth. 15 In N. pharaonis, which grows optimally at pH 9.0-10.0, BR is lacking and instead HR participates in the generation of metabolic energy.…”
Section: Introductionmentioning
confidence: 99%
“…This property has simplified the analysis of the anion-transporting photocycle of p HR, which is usually described by the following scheme: p HR + hν → K→ L1 → L2 → N → O → p HR′ → p HR ( 18,23,24 ). From time-resolved absorption and electric measurements, it was suggested that anion release into the cytoplasmic medium takes place during the N-to-O transition, whereas anion uptake from the extracellular medium occurs in the decay of the O state ( 24–26 ). (Although p HR′ was introduced to explain the biphasic decay of O observed in bacterioruberin-free samples of p HR, this reaction state was not always detected in the anion-pumping cycle of the trimeric p HR-bacterioruberin complex, the structure of which is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%